CAPTURA Regional Workshop Proceedings (28-30 June 2022, Virtual) - Joh, Hea Sun; Dolabella, Brooke; Early, Emmanuel; Stelling, John; Ak, Gabriella; Upadhyaya, Madan Kumar; Rahman, Aninda; Chuki, Pem; MacWright, William R; Ondoa, Pascale; Sarkar, Satyajit; Moore, Catrin; et al. (Clinical infectious diseases, 2023)
In response to the global threat of antimicrobial resistance (AMR), the Capturing Data on Antimicrobial Resistance Patterns and Trends in Use in Regions of Asia (CAPTURA) project worked with microbiology laboratories, pharmacies, and local governments in South Asia and Southeast Asia to expand the volume of historical and current data available on AMR and antimicrobial use and to identify gaps in data and areas for quality improvement. When the CAPTURA project completed its country-level engagement in the first half of 2022, the consortium brought together local, regional, and global AMR stakeholders for a virtual regional workshop to review data outputs from the project and share strategies to inform national and regional efforts to combat AMR. This paper summarizes the main topics presented in the workshop held from 28 to 30 June 2022. As such, it highlights lessons learned from the project and strategies to fight AMR. Although CAPTURA has been invaluable to countries and information from the project is already being used, barriers concerning data quality and sharing remain. Regional-level initiatives should continue to build on the momentum gained from the CAPTURA project in supporting national-level surveillance and data quality improvements to inform critical decisions around planning, policies, and clinical care. Project findings have highlighted that issues with antimicrobial resistance and use are wide ranging across countries. Going forward, building on the current foundations and tailoring approaches to meet local needs and capacities will be fundamental in combatting AMR.